Leptin: A Potential Link Between Obstructive Sleep Apnea and Obesity - Ciriello, John; Moreau, Jason M.; Caverson, Monica M.; Moranis, Rebecca (Frontiers in Physiology, 2022)
Chronic intermittent hypoxia (CIH), a pathophysiological manifestation of obstructive sleep apnea (OSA), is strongly correlated with obesity, as patients with the disease experience weight gain while exhibiting elevated plasma levels of leptin. This study was done to determine whether a relationship may exist between CIH and obesity, and body energy balance and leptin signaling during CIH. Sprague-Dawley rats were exposed to 96 days of CIH or normoxic control conditions, and were assessed for measures of body weight, food and water intake, and food conversion efficiency. At the completion of the study leptin sensitivity, locomotor activity, fat pad mass and plasma leptin levels were determined within each group. Additionally, the hypothalamic arcuate nucleus (ARC) was isolated and assessed for changes in the expression of proteins associated with leptin receptor signaling. CIH animals were found to have reduced locomotor activity and food conversion efficiency. Additionally, the CIH group had increased food and water intake over the study period and had a higher body weight compared to normoxic controls at the end of the study. Basal plasma concentrations of leptin were significantly elevated in CIH exposed animals. To test whether a resistance to leptin may have occurred in the CIH animals due to the elevated plasma levels of leptin, an acute exogenous (ip) leptin (0.04 mg/kg carrier-free recombinant rat leptin) injection was administered to the normoxic and CIH exposed animals. Leptin injections into the normoxic controls reduced their food intake, whereas CIH animals did not alter their food intake compared to vehicle injected CIH animals. Within ARC, CIH animals had reduced protein expression of the short form of the obese (leptin) receptor (isoform OBR100) and showed a trend toward an elevated protein expression of the long form of obese (leptin) receptor (OBRb). In addition, pro-opiomelanocortin (POMC) protein expression was reduced, but increased expression of the phosphorylated extracellular-signal-regulated kinase 1/2 (pERK1/2) and of the suppressor of cytokine signaling 3 (SOCS3) proteins was observed in the CIH group, with little change in phosphorylated signal transducer and activator of transcription 3 (pSTAT3). Taken together, these data suggest that long-term exposure to CIH, as seen in obstructive sleep apnea, may contribute to a state of leptin resistance promoting an increase in body weight.